The timing of umbilical cord clamping at birth: physiological considerations. Issue 1 (December 2016) - Hooper, Stuart; Binder-Heschl, Corinna; Polglase, Graeme; Gill, Andrew; Kluckow, Martin; Wallace, Euan; Blank, Douglas; te Pas, Arjan
Abstract While it is now recognized that umbilical cord clamping (UCC) at birth is not necessarily an innocuous act, there is still much confusion concerning the potential benefits and harms of this common procedure. It is most commonly assumed that delaying UCC will automatically result in a time-dependent net placental-to-infant blood transfusion, irrespective of the infant's physiological state. Whether or not this occurs, will likely depend on the infant's physiological state and not on the amount of time that has elapsed between birth and umbilical cord clamping (UCC). However, we believe that this is an overly simplistic view of what can occur during delayed UCC and ignores the benefits associated with maintaining the infant's venous return and cardiac output during transition. Recent experimental evidence and observations in humans have provided compelling evidence to demonstrate that time is not a major factor influencing placental-to-infant blood transfusion after birth. Indeed, there are many factors that influence blood flow in the umbilical vessels after birth, which depending on the dominating factors could potentially result in infant-to-placental blood transfusion. The most dominant factors that influence umbilical artery and venous blood flows after birth are lung aeration, spontaneous inspirations, crying and uterine contractions. It is still not entirely clear whether gravity differentially alters umbilical artery and venous flows, although the available data suggests that its influence, if present, is minimal. While there is much support for delaying UCC at birth, much of the debate has focused on a time-based approach, which we believe is misguided. While a time-based approach is much easier and convenient for the caregiver, ignoring the infant's physiology during delayed UCC can potentially be counter-productive for the infant.